Aleukemic myeloid sarcoma of small intestine: masquerading as subacute intestinal obstruction: Review of literature - Joshi, Vidushi; Gahlot, Gaurav PS; Ahuja, Ankur; Chatterjee, Tathagata; BS, Sunita (Annals of Pathology and Laboratory Medicine, 2020)
Background: Myeloid sarcoma (MS) is an extramedullary disease of immature myeloid cells with incidence of 1-2% among all acute myeloid leukemia (AML) cases. Less than twenty cases of aleukemic MS with initial presentation as intestinal mass have been described in the English literature. Case report: Here we report a case of 45 year old female with normal haematology workup who presented with acute abdominal pain and distension. On evaluation, she was found to have ileocolic intussusception of gangrenous bowel, so managed by limited right hemicolectomy and initially reported as Non Hodgkin lymphoma (NHL).During follow-up she was found to have a globular mass in right lumbar region that was diagnosed as myeloid sarcoma. On further followup, her TLC count was gradually increasing. Conclusion: The index case highlights the unusual presentation of isolated intraabdominal MS which was clinical diagnosed as subacute intestinal obstruction in a young female with normal hematological profile.